Od "Płatonowa" do Sachalina - Ksenicz, Andrzej (Rusycystyczne Studia Literaturoznawcze, 2016)
The author attempts to specify the facts related to the publications and the reaction of criticism to the first dramatic writings by Czekhov. The young author had to break the old canons of dramatical art, which led to a strong reaction of the supporters of the traditional understanding of drama. This is exemplified by the history of the “Ivanov” performance.